Family law in France: A law in transformation - Želčević-Diamel Ana (Anali Pravnog Fakulteta u Beogradu)
The French family law is the expression of some substantial changes that are taking place in the French society. They concern both marriage and relationships between parents and children. It is also possible to notice a growing interest of the European law, through the right of privacy, specially regarding the freedom of marriage and the question of surrogate mothers. Also, since 2016 French law admits the mutual consent divorce without a judge.